Assessment of Selected Radio Jingles in Promoting Peaceful Co-Existence Among Residents of Plateau State, Nigeria - Dimka, Nit Dafaan; Kente, Josiah Sabo; Akpede, K. S. (International Journal of Education, Culture, and Society, 2025)
This study assesses the effectiveness of select PRTVC radio jingles in promoting peaceful co-existence among residents of Plateau State, Nigeria. Guided by Social Judgement Theory, the research sought to (1) determine the role of radio jingles in fostering peace and (2) identify the content elements considered relevant by residents in encouraging peaceful co-existence. Employing a survey design, data were collected from 400 randomly selected respondents in Jos metropolis, with the sample size determined using the Taro Yamane technique. The reliability of the instruments was tested using Cronbach’s Alpha, while Principal Component Analysis (PCA) and descriptive statistics were applied in the analysis. The findings indicate that while PRTVC radio jingles play a role in promoting peaceful co-existence, their effectiveness is limited by several challenges. The study concludes that for jingles to serve as impactful tools of peacebuilding, they must incorporate thematic, participatory, and unbiased content. It recommends stronger collaboration between PRTVC, the Plateau State Government, and other stakeholders to enhance peacebuilding initiatives, alongside improved content design for radio jingles to maximize audience engagement and effectiveness.